2002
DOI: 10.1063/1.1494118
|View full text |Cite
|
Sign up to set email alerts
|

Point-defect influence on 1/f noise in HgCdTe photodiodes

Abstract: Articles you may be interested inThe role of localized junction leakage in the temperature-dependent laser-beam-induced current spectra for HgCdTe infrared focal plane array photodiodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…According to theoretical investigations [32], a charged defect V O 2+ having a large energy barrier of 0.2 eV can be photoionized by UV excitation and, thus, donate two electrons to the NW; therefore, positively charged defects play a role similar to that of charged scattering centers in semiconductors. Hooge's constant is strongly correlated with the concentration of ionized defects in a material [41], as well as the presence of charged defects [14] and/or surface charged species [40]. Accordingly, the value of Hooge's constant in our NW phototransistors would be enhanced under UV excitation.…”
Section: S I / I Dmentioning
confidence: 89%
“…According to theoretical investigations [32], a charged defect V O 2+ having a large energy barrier of 0.2 eV can be photoionized by UV excitation and, thus, donate two electrons to the NW; therefore, positively charged defects play a role similar to that of charged scattering centers in semiconductors. Hooge's constant is strongly correlated with the concentration of ionized defects in a material [41], as well as the presence of charged defects [14] and/or surface charged species [40]. Accordingly, the value of Hooge's constant in our NW phototransistors would be enhanced under UV excitation.…”
Section: S I / I Dmentioning
confidence: 89%
“…Since 1/f noise is important in IR imaging systems, which usually operate at low frame rates, it is worth mentioning that Mainzer et al 107 found, using n + p diodes fabricated by SCD in vacancy-doped LPE grown HgCdTe layers, that the 1/f noise depended linearly on the fraction of ionized point defects. The total point-defect concentration was extracted from the comparison of the absolute lattice parameter accurately measured by high-resolution X-ray diffraction, with the lattice parameter expected from the Cd content as determined from the Fourier transform infrared transmission curve.…”
Section: Nonideal Behavior In Hgcdte Photodiodes -Tunneling Effectsmentioning
confidence: 99%
“…或迁移率的涨落, 最终形成探测器噪声的重要来 源 [30][31][32] . 碲镉汞红外焦平面工作在光伏型、电流模式, 其暗电流以及相关噪声水平是决定其探测器灵敏度的 关键要素, 它决定了红外系统对目标的探测、跟踪和 识别能力 [33] .…”
Section: 另外 无论采用液相外延的平衡态生长方法还是unclassified